2018
DOI: 10.1002/jia2.25108
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the HIV treatment gap in Nigeria: examining community antiretroviral treatment models

Abstract: IntroductionSignificant gaps persist in providing HIV treatment to all who are in need. Restricting care delivery to healthcare facilities will continue to perpetuate this gap in limited resource settings. We assessed a large‐scale community‐based programme for effectiveness in identifying people living with HIV and linking them to antiretroviral treatment.MethodsA retrospective secular trend study of 14 high burden local government areas of Nigeria was conducted in which two models of community antiretroviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Data from general adult population cohort studies have shown better uptake and time to viral suppression among those initiating ART early compared to more delayed ART initiation, and no difference in retention in care in the one cohort reporting on this outcome (Pilcher 2017). Oladele 2018 evaluated different rapid ART delivery methods and determined that community‐based rapid ART was more effective than referral for facility‐based rapid ART. Among pregnant women, same‐day ART initiation appeared to result in similar retention or viral suppression compared to delayed treatment (median seven days; Langwenya 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Data from general adult population cohort studies have shown better uptake and time to viral suppression among those initiating ART early compared to more delayed ART initiation, and no difference in retention in care in the one cohort reporting on this outcome (Pilcher 2017). Oladele 2018 evaluated different rapid ART delivery methods and determined that community‐based rapid ART was more effective than referral for facility‐based rapid ART. Among pregnant women, same‐day ART initiation appeared to result in similar retention or viral suppression compared to delayed treatment (median seven days; Langwenya 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Gradual decentralisation since then has resulted in an increased mix in types and levels of healthcare facilities delivering HIV services. 26 While this has significantly increased access to HIV services, it has also brought about heterogeneity in terms of how national HIV guidelines are interpreted and implemented. The extent to which these differences in service delivery channels have shaped HIV-related outcomes have received little attention partly because of little information sharing between the public and private health sectors.…”
mentioning
confidence: 99%
“…The significance of the study results is the fact that the CTI, as an intervention, improved ART uptake in the community and could therefore be used in rural communities. Low-and middle-income countries thatoften battlewith poor health infrastructure underpinned by poor human resource for health (HRH) will benefit from community interventions in order to control the HIV epidemic (Oladele et al, 2018). The conventional method for ART includes self/community referrals to the facility, the use of linkage coordinators/escort services, and redeemable coupons as an incentive for linkage.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that this study will contribute to the body of knowledge by providing evidence on how a community intervention such as a CTI can ensure that PLHIV who refuse treatment at the facility for one reason or another are placed on treatment in the community (Busza et al, 2018;Oladele et al, 2018). Additionally, this study presents the CTI as an alternative treatment method in a resource-poor setting such as Nigeria.…”
Section: Added Value Of This Studymentioning
confidence: 97%